Aminopyridine derivatives controlled the assembly and various properties of Cu–BTC metal–organic frameworks1. Issue 31 (21st August 2015) - Wang, Xiuli; Le, Mao; Lin, Hongyan; Luan, Jian; Liu, Guocheng; Liu, Danna
<x xml:space="preserve">Abstract</x> Three Cu(ii) MOFs based on three aminopyridine derivatives and 1, 3, 5-benzenetricarboxylic acid have been synthesized and characterized. The electrocatalytic and photocatalytic properties of complexes 1–3 have been investigated in detail.